PENGHAPUSAN BATAS WAKTU MAKSIMAL PENCABUTAN HAK POLITIK TERHADAP TERPIDANA KORUPSI DALAM UPAYA PEMBERANTASAN TINDAK PIDANA KORUPSI - Shobirin, Muhamad Allwin; Fitriana, Mohamad Noor Fajar Al Arif; Asphianto, Aan (SINERGI : Jurnal Riset Ilmiah, 2025)
Corruption is an extraordinary crime that not only harms the state's finances but also undermines public trust and damages the democratic system. In addressing this issue, Indonesia has implemented various efforts to combat corruption; however, many public officials continue to be involved in corrupt practices. One preventive measure in the eradication of corruption is the imposition of an additional criminal sanction in the form of the revocation of political rights for corruption convicts. This research identifies and analyzes the implementation of political rights revocation for corruption convicts within the Indonesian criminal law system, as well as the abolition of the maximum time limit for such revocation as part of efforts to eradicate corruption in Indonesia. This study employs a normative juridical method with a statutory approach, analyzed through the theory of legal certainty and the theory of justice. The findings indicate that the revocation of political rights plays a strategic role in creating a deterrent effect, preventing former corruption convicts from running for public office, and preserving the integrity of elections. Therefore, legal reform is necessary in the form of explicit regulation regarding the permanent revocation of political rights for corruption convicts not only as a progressive legal policy, but also as a manifestation of the state's responsibility to build a clean, just, and integrity-based system of governance.